Effects of exercise on perceptual estimation and short-term recall of shooting performance in a biathlon - Grebot, C.; Groslambert, A.; Pernin, J. N.; Burtheret, A.; Rouillon, J. D. (Perceptual and Motor Skills, 2003)
Little is known about the effects of exercise on cognitive function, but in a biathlon it is known that intense skiing exercise decreases shooting performance. So the present study was designed to assess the cognitive origin of this decrease by examining the influence of skiing exercise on perceptual estimation and short-term verbal recall of shooting performance in a biathlon. 10 elite biathletes (6 men, 4 women) performed five trials of five shots in standing position in two conditions, at rest and after a standardised skiing exercise. At the end of each trial, the shooting performance was investigated by measuring the actual shooting performance and the perceptual estimation of the shooting performance. A two-way analysis of variance and the effect size indicated a significant decrease in shooting performance after skiing, but none between the actual and estimated shooting performance. At rest .4% of the shots were not estimated (1 out of 250), whereas after exercise the biathletes were not able to estimate 4.8% of the shots (12 out of 250). Further, only .01% of the nonestimated shots after exercise missed the target, i.e., 3 out of 250. The results suggest that the perceptual estimation of the shooting is not significantly affected by skiing exercise and do not explain the decrease in shooting performance observed after intense exercise. However, intense exercise could increase the difficulty of recall shooting performance and may force biathletes to use their memory selectively.